Visual dominance and visual egalitarianism: individual and group-level influences of sex and status in group interactions - Koch, Sabine C.; Baehne, Christina G.; Kruse-Graumann, Lenelis; Zimmermann, Friederike; Zumbach, Joerg (Journal of nonverbal behavior, 2010)
This study investigated visual dominance and visual egalitarianism of men and women (N = 94; 17 teams) in team meetings at diverse workplaces. Two novel gaze-related measures were developed: (a) a group visual dominance ratio (group-VDR) assessing each member’s visual dominance vis-à-vis all other members, and (b) a gaze distribution index (GDI) assessing each member’s visual egalitarianism to all group members. Multilevel analyses were conducted to account for influences of the team members’ sex and status on the individual level and for influences of sex and status composition of the teams, and the team leaders’ sex on the group level. Results suggested that high-status individuals displayed more visual dominance than low-status individuals. The significant interaction of individuals’ sex and status indicated that the positive relationship of status and visual dominance applied particularly to women. The more women in a team, the more visual dominance was displayed. The team leader’s sex significantly influenced visual egalitarianism: Gaze distribution was less egalitarian when the team leader was male.